Integration of Temperature and Power Data Acquisition Using Modbus RTU RS485 Communication for Performance Monitoring of Thermoelectric Cooler Box - Sujana, I Komang; Winarta, Adi (Journal of Global Engineering Research and Science, 2024)
This study presents the design and implementation of a real-time data acquisition and monitoring system for a thermoelectric cooler box integrated with Phase Change Material (PCM) for thermal storage. The novel contribution of this research is the combined use of Modbus RTU RS485-based communication and real-time SCADA logging, enabling simultaneous monitoring of thermal and electrical performance. At the core of the system is the Haiwell SCADA application, which provides a user-friendly interface for continuous data visualization, logging, and fault detection. During the configuration phase, Modbus Poll is used to assign IP addresses and ensure communication integrity among the devices. The hardware setup consists of a laptop interface, an RS485 hub, and multiple slave devices, including thermocouples, NTC sensors, and power meters, all interconnected via structured wiring. Real-time power monitoring using PZEM-017 modules confirmed stable electrical performance, with brief transient drops during resets or manual interventions that quickly stabilized, demonstrating system resilience. This integration supports transient event tracking, performance degradation analysis, and improved diagnostics over time. Additionally, the system enables detailed performance mapping, facilitating proactive maintenance and optimization of cooling performance under varying loads.